La danza académica en Honduras - Buck-Rodríguez, Sara (2020)
This article reviews the history of Studio Danzarte in Siguatepeque, and addresses some issues about the development of academic dance in Honduras, its link with Costa Rican dance and its projection into the community, considering dance as a tool for individual and collective education, as an artistic expression from Central America.